Default Risk Premia on Government Bonds in a Quantitative Macroeconomic Model - Falko Juessen; Ludger Linnemann; Andreas Schabert (Tinbergen Institute, 2009)
This paper examines the pricing of public debt in a quantitative macroeconomic model with government default risk. Default may occur due to a fiscal policy that does not preclude a Ponzi game. When a build-up of public debt makes this outcome inevitable, households stop lending such that the government has to default. Interest rates on government bonds reflect expectations of this event. There may exist multiple bond prices compatible with a rational expectations equilibrium. We analyze the conditions under which expected default risk premia can quantitatively rationalize sizeable spreads on public bonds. Sovereign default risk premia turn out to emerge at either very high debt to output ratios, or if the variance of productivity shocks is large.
Keywords: E62; G12; H6; E32; 330; Sovereign default; asset pricing; fiscal policy; government debt; Öffentliche Anleihe; Risikoprämie; Insolvenz; Öffentliche Schulden; Finanzpolitik; Makroökonomik; Theorie